THE CARAVANSERAIS DURING THE REIGN OF THE GREAT SELJUKS (1038-1157) - Rajapov Pirnazar Sardor ogli (Galaxy International Interdisciplinary Research Journal, 2024)
This article provides information about the caravanserais of the Great Seljuk period (1038-1157). The caravanserais of Rabati Anushirvan, Rabati Zafaran and Rabati Sharif in the Khurasan region, and partly on the caravanserais of Kirman and other regions were touched upon. Also, It is paid attention to the architectural tradition of Seljuk era caravanserais, in particular, the features of the building, such as construction materials. Also, constructions such as rabat, khan, zawiya, takya, khanqah, which are the equivalent of a caravanserai, and their functions are explained.